2020
DOI: 10.1101/2020.06.04.132753
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of rare transient somatic cell states induced by injury and required for whole-body regeneration

Abstract: Regeneration requires functional coordination of stem cells, their progeny, and differentiated cells. Past studies have focused on regulation of stem cell identity and proliferation near to the wound-site, but less is known about contributions made by differentiated cells distant to the injury. Here, we present a comprehensive atlas of whole-body regeneration over time and identify rare, transient, somatic cell states induced by injury and required for regeneration. To characterize amputation-specific signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 92 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…Methods have been developed to use scRNA-seq to characterize cell populations and track distinct cell lineages during embryonic development (e.g., [153,154]). These approaches have also been used to understand regeneration processes in different species across the animal kingdom, including WBR in the planarian Schmidtea [155][156][157][158][159][160], anterior body regeneration in the earthworm Eisenia [161], tail regeneration in Xenopus [162,163], leg regeneration in the axolotl Ambystoma [164][165][166], fin and heart regeneration in zebrafish [167][168][169], and digit regeneration in mice [170][171][172][173].…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods have been developed to use scRNA-seq to characterize cell populations and track distinct cell lineages during embryonic development (e.g., [153,154]). These approaches have also been used to understand regeneration processes in different species across the animal kingdom, including WBR in the planarian Schmidtea [155][156][157][158][159][160], anterior body regeneration in the earthworm Eisenia [161], tail regeneration in Xenopus [162,163], leg regeneration in the axolotl Ambystoma [164][165][166], fin and heart regeneration in zebrafish [167][168][169], and digit regeneration in mice [170][171][172][173].…”
Section: Perspectivesmentioning
confidence: 99%
“…These studies revealed the diversity of cell populations during regeneration and unveiled previously unrecognized cell types in the blastema, such as multipotent mesenchymal-like progenitors producing various connective tissue lineages during axolotl limb regeneration [164,165], regeneration-organizing cells which belong to the wound epidermis and act as a signaling center during Xenopus tail regeneration [162], or rare and transient cell types required for WBR in Schmidtea [160]. Another very promising path to further unravel regeneration mechanisms is to combine mRNA-seq (both bulk and scRNA-seq) with epigenomic approaches.…”
Section: Perspectivesmentioning
confidence: 99%
“…Because chemical pharynx removal does not increase production of neural tissue ( Figure 1—figure supplement 1B,C ), while its surgical removal does ( LoCascio et al, 2017 ), non-targeted regenerative mechanisms may require injury to specific types of tissues, such as body-wall muscle, epithelia, or intestine. In fact, amputation-specific transcriptional changes important for regeneration have recently been identified within these tissues ( Witchley et al, 2013 ; Lander and Petersen, 2016 ; Scimone et al, 2016 ; Benham-Pyle et al, 2020 ). These results suggest that while cells generated immediately after tissue removal can be broadly deployed to all surrounding tissues, those generated 1 day later are targeted toward only those that are missing.…”
Section: Resultsmentioning
confidence: 99%
“…Regulatory signals could either be produced upon injury to promote regeneration, or released from inhibitory cues that might emanate from organs when they are present ( Rink, 2018 ; Ziller-Sengel, 1967 ; Ziller-Sengel, 1965 ). Intriguingly, a recent study characterizing transient amputation-induced transcriptional changes revealed that the majority of these changes occur within differentiated cell types ( Benham-Pyle et al, 2020 ). The possibility of transient signals customized to particular organs and the ability of stem cells to readily sense them may explain how planarians exhibit such rapid and robust regeneration of all organs.…”
Section: Discussionmentioning
confidence: 99%